CHALLENGE OF WATER SHORTAGE IN THE WORLD AND AZERBAIJAN AND SCIENTIFIC PRACTICAL SOLUTION - Aliyev, RAE. Z.H. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2017)
The rapid growth in world population and limitation of soil and water resources have caused major problem for human nutrition security in the world. only 3% of water resources are fresh water. Accoding to the FAO report, if in the any country Amount of fresh water is less than 1700m3 per capita, this country is faced to serous water shortage. At the present, in the 22 countries share of fresh water per capita is less than 100m3and in the 18 countries is more than 2000m3. Therefore, Azerbaijan is one of the countries which have faced serous water shortage.